2013
DOI: 10.1021/ie4006194
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solvents on De-Cross-Linking of Cross-Linked Polyethylene under Subcritical and Supercritical Conditions

Abstract: The effect of various solvents on the de-cross-linking reaction of cross-linked polyethylene under subcritical and supercritical conditions was studied. The gel content of the de-cross-linked polyethylene decreased from 60 to 0.8–2.5% at 380 °C within 5 min in all of the solvents tested in this study. When water, ethanol, and 2-propanol were used, the M w of the de-cross-linked polyethylenes decreased from 349,000 to 200,000–227,000 g/mol, and much lower M w values of 70,000–90,000 g/mol were observed when ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…The observation indicates that XLPE is basically decrosslinked because of thermal dissociation of the C–C bonding and the supercritical methanol conditions accelerate the decrosslinking reaction. These results are well in agreement with those reported from the batch reaction . However, the continuous supercritical extrusion process resulted in lower degree of decrosslinking effect than that of the batch type reactor…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The observation indicates that XLPE is basically decrosslinked because of thermal dissociation of the C–C bonding and the supercritical methanol conditions accelerate the decrosslinking reaction. These results are well in agreement with those reported from the batch reaction . However, the continuous supercritical extrusion process resulted in lower degree of decrosslinking effect than that of the batch type reactor…”
Section: Resultssupporting
confidence: 92%
“…Goto et al reported that silane‐XLPE could be depolymerized through selective decomposition of the siloxane bonds in supercritical methanol or water . In our previous studies, we also observed that the irradiation‐crosslinked, the silane‐crosslinked, and the peroxide‐crosslinked PE could successively be decrosslinked into the thermoplastic PE using supercritical methanol . The decrosslinking reaction rate was observed as linearly proportional to the gel content and exponentially related to the reaction temperature.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…Since the value of M n is not available, the weight average molecular weight, M w of HDPE is used in calculation of eqn (2). The M w of HDPE is 5.2 Â 10 4 g mol À1 .…”
Section: Gel Fraction and Crosslink Densitymentioning
confidence: 99%